Ingresos públicos por recursos determinados y el gasto público en bienes y servicios en la Municipalidad Distrital de Belén, periodo 2019 – 2023 - Mori Garcia, Gilary Thalia (2025)
The present investigation is called "Public Income from determined resources and public spending on goods and services in the District Municipality of Belén, period 2019 - 2023", focusing its attention on determining the relationship between income with public expenses, the scope of Its population was five (05) years old and included all the information linked to public income and public expenses of the aforementioned municipality, and in order to meet its objectives, techniques such as tabulation, analysis, selective review were used. and survey; The methodology follows a quantitative approach, at a descriptive - correlational level, with a non-experimental - longitudinal design. Finally, the results achieved reveal that there is a very high positive relationship between public resource revenue and public spending, which can be confirmed in the value of Spearman's Rho correlation coefficient calculated at 0.946.